Impact of the COVID‐19 pandemic on urological cancers: The surgical experience of two cancer hubs in London and Milan. Issue 4 (27th January 2022) - Monroy‐Iglesias, Maria J.; Rai, Sonpreet; Mistretta, Francesco A.; Roberts, Graham; Dickinson, Harvey; Russell, Beth; Moss, Charlotte; De Berardinis, Rita; Ferro, Matteo; Musi, Gennaro; Brown, Christian; Nair, Rajesh; et al.
Abstract: Objective: To report on the outcomes of urological cancer patients undergoing radical surgery between March–September 2020 (compared with 2019) in the European Institute of Oncology (IEO) in Milan and the South East London Cancer Alliance (SELCA). Materials and Methods: Since March 2020, both institutions implemented a COVID‐19 minimal 'green' pathway, whereby patients were required to isolate for 14 days prior to admission and report a negative COVID‐19 polymerase chain reaction (PCR) test within 3 days of surgery. COVID‐19 positive patients had surgery deferred until a negative swab. Surgical outcomes assessed were: American Society of Anaesthesiologists (ASA) grade; surgery time; theatre time; intensive care unit (ICU) stay >24 h; pneumonia; length of stay (LOS); re‐admission. Postoperative COVID‐19 infection rates and associated mortality were also recorded. Results: At IEO, uro‐oncological surgery increased by 4%, as compared with the same period in 2019 ( n  = 515 vs. 534). The main increase was observed for renal (16%, n  = 98 vs. 114), bladder (24%, n  = 45 vs. 56) and testicular (27%, n  = 26 vs. 33). Patient demographics were all comparable between 2019 and 2020. Only one bladder cancer patient developed COVID‐19, reporting mild/moderate disease. There was no COVID‐19 associated mortality. In the SELCA cohort, uro‐oncological surgery declined by 23% ( n  = 403 vs. 312) compared with the previous year. The biggest decrease was seen for prostate (−42%, n  = 156 vs. 91), penile (−100%, n  = 4 vs. 0) and testicular cancers (−46%, n  = 35 vs. 24). Various patient demographic characteristics were notably different when comparing 2020 versus 2019. This likely reflects the clinical decision of deferring COVID‐19 vulnerable patients. One patient developed COVID‐19, with no COVID‐19 related mortality. Conclusion: The COVID‐19 minimal 'green' pathways that were put in place have shown to be safe for uro‐oncological patients requiring radical surgery. There were limited complications, almost no peri‐operative COVID‐19 infection and no COVID‐19‐related mortality in either cohort.